Generasi Millennial Dalam Tujuan SDG’s: Tujuan Pekerjaan Layak Dan Pertumbuhan Ekonomi (Studi Kasus Mahasiswa Universitas Mulawarman) - Aisyah Trees Sandy; Anggraini, Afra Salimah; Khalisa, Selvi Nur; Jusmawati, Jusmawati; Ratnawati, Endang; Rahmadi, Rahmadi; Juwari, Juwari (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
The Millennial Generation is an indicator that is expected to be able to compete in the digital era and be able to create a golden generation in 2045. This research aims to describe the opinions of the millennial generation regarding the SDG's goals: decent work goals and economic growth (case study of Mulawarman University students). The research method used is descriptive. Data collection techniques use questionnaires and documentation. Data analysis techniques use Miles and Huberman. The results of research from 344 respondents showed that 71% of Mulawarman University students were interested in entering the world of work after graduating from college and the percentage of becoming employees was 38.2%, 30.3% opened up employment opportunities and 31.5% chose others. Mulawarman University students have a very high level of worry about the future which also influences their thinking patterns, namely 85% and often compare themselves with other people, namely 61.5%. Opinions on how to realize SD's goals of decent work and economic growth by providing opinions about interests and promising economic sectors in the future, namely agriculture at 9%, animal husbandry 18.9%, mining 2.9%, technology and digital 35.2% , finance 1.5%, trade 2.9%, health 19.5%, fashion 1.7%, plantations 2%, others 6.4%. The research results show that Mulawarman University students' opinions regarding decent work and economic growth in the future are more about utilizing technology and digital.